(untitled) (Journal of Legal Studies, 2017)
The year 1991, the year when the current Romanian fundamental law came in to force, designed a constitutional moment built on profound political and societal emotions. These emotions pushed the Constituent Assembly in search of an answer, in the form of a solution, to the question "What do we not want?" The answer was: "An authoritarian president / chief of state!" Consequently, the position of the head of state in the political scaffolding received an increased attention. Unlike the Communist president, who exercised great powers, the new president was thought and designed antagonistic to his predecessor. He was reduced to a role of a simple mediator. However, more than 20 years after the fall of the communist regime, the "traditional" authoritarian personality of the president transcended - of course, not as pronounced as in the communist era - the finality of the presidential role and of the presidential attributions stated in the Constitution. As we shall see, the "player president" emerged and got confirmed by the Romanian Constitutional Court against the desideratum of the constitutional moment of 1991.